Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Produksi Petani Garam Di Kabupaten Pamekasan - Laili Nur Rahmawati; Prasetyo Nugroho (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this research is to find out how much influence capital, labor, land area, length of business, and weather have on the production level of salt farmers in Pamekasan Regency. Data collection techniques obtained in this study were obtained and primary data in the form of Questionnaires distributed directly to salt farmers in Pamekasan Regency. The sample used was 50 respondents. The technique used in sampling is the Slovin formula with random sampling without showing the existing strata. The results of this study indicate 1) it is concluded that working capital has a positive and significant effect on the level of production, with a t value of 2.675 and sig 0.001 0.05, 2) labor has no significant effect on the level of production with a value of 1 count of 0.526 and 0.602 3) capital work has a positive and significant effect on the level of production with a t- count value of 5.904 and a significant amount of 0.000 0.05 3) length of work has a positive and significant effect on farmers' production levels with a t-count value of 2.605 and a significant amount of 0.012 0.05 4) weather has a positive and significant effect to the level of production with a t value of 2,343 and a significant level of 0.21 0.05